Foundations for a Theological Aesthetics in Thomas Aquinas. - Ramos, Alice M. (Scripta Mediaevalia, 2025)
God's self-revelation in the universe is due to His creation of all things through the Word or the Logos; creation so conceived is revelatory or expressive of its maker. It is the case, however, that the images and traces of God's presence in the universe are not always perceived, leading at times to his denial. We will then investigate some of the reasons or causes for man's obscured vision. Man's vision or understanding requires healing if he is to attain his final end, and so we will speak of the need of the Incarnation which makes possible not only the restoration of man's vision or understanding but also that most sublime elevation of the human person to a participation in God's very life. And this process of divinization will also have repercussions for the state of the universe, since at the end of time the universe will be made a fitting dwelling place for men so perfected. My interest, then, will be in the three stages of salvation history: creation, redemption, and the parousia. At each of these stages we will see how beauty is at work, for God intends his creation to be ultimately a definitive theophany, a manifestation of God's glory, of his beauty.